Unexpected Dimer from Demethylization Reaction of Eugenol under Acidic Conditions - Anita Alni; Meilisa Dara Puspita; Didin Mujahidin (Journal of Mathematical and Fundamental Sciences, 2019)
Eugenol is an alkenyl phenol compound obtained as an essential oil from different parts of the clove such as its leaves and flowers. The essential oil from cloves can contain up to 90% eugenol, which is mainly responsible for its aroma. Eugenol is an interesting compound due to its simplicity and richness in functionalities, making it a valuable building block in synthesis. One of the key steps in eugenol transformation is demethylation to produce a hydroxycavicol. Demethylation is commonly carried out using a nucleophilic or an acidic method. In this study, a simple yet reliable nucleophilic method for demethylation using lithium chloride (LiCl) was attempted. The product was characterized by NMR, FTIR and HRMS spectroscopy. The absence of a methoxy signal at 3.5-4 ppm in the 1H NMR spectrum suggests that demethylation was successful. The HRMS result showed m/z 149.0596, confirming the formation of product. The demethylation reaction under acidic conditions formed a dimer of eugenol with the methoxy group still intact. This was supported by the 1H NMR data, which showed methoxy signals at 3.85 and 3.82 ppm and integration in the aromatic region, which suggests a dimer structure.